2006
DOI: 10.1002/cncr.22050
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial to improve early detection and prevention practices among siblings of melanoma patients

Abstract: Disease overview POEMS syndrome is a paraneoplastic syndrome due to an underlying plasma cell neoplasm. The major criteria for the syndrome are polyradiculoneuropathy, clonal plasma cell disorder (PCD), sclerotic bone lesions, elevated vascular endothelial growth factor, and the presence of Castleman disease. Minor features include organomegaly, endocrinopathy, characteristic skin changes, papilledema, extravascular volume overload, and thrombocytosis. Diagnoses are often delayed because the syndrome is rare a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
94
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 77 publications
(102 citation statements)
references
References 121 publications
4
94
2
Order By: Relevance
“…The number of participants in both groups that received a skin cancer examination more than doubled, with no differences between intervention and control subjects. 92 Earlier surveys on beliefs and practices regarding skin cancer prevention and detection among 404 siblings of recently diagnosed patients with melanoma found that only 27% had received a skin cancer examination by a dermatologist during the past year; 47% had never received a dermatologic examination. Multivariate analysis found modifiable positive predictors for SSE and dermatologist examinations, including having a clinician with whom to talk about melanoma and believing in the importance of regular skin examinations by a physician.…”
Section: Populations At High Riskmentioning
confidence: 99%
“…The number of participants in both groups that received a skin cancer examination more than doubled, with no differences between intervention and control subjects. 92 Earlier surveys on beliefs and practices regarding skin cancer prevention and detection among 404 siblings of recently diagnosed patients with melanoma found that only 27% had received a skin cancer examination by a dermatologist during the past year; 47% had never received a dermatologic examination. Multivariate analysis found modifiable positive predictors for SSE and dermatologist examinations, including having a clinician with whom to talk about melanoma and believing in the importance of regular skin examinations by a physician.…”
Section: Populations At High Riskmentioning
confidence: 99%
“…Geller et al demonstrated in a randomized control trial that siblings of melanoma patients who had received an intervention were more likely to examine all their moles 12 months later, including the ones on their backs. 47 Skin selfexamination has a role in reducing melanoma mortality; as Berwick et al demonstrated, it could potentially reduce mortality related to melanoma by 63%. 48 Indeed, in a study in New York, skin selfexamination was found to be a key predictor of presentation with a melanoma <1 mm in thickness.…”
Section: Epidemiology Diagnosis Screening and Prognosismentioning
confidence: 99%
“…In a study of unaffected first-degree relatives of individuals diagnosed with melanoma, it was reported that less than one-third practiced sun protective behaviors such as using sunscreen routinely, staying in the shade, and wearing protective clothing frequently [7]. Furthermore, in an intervention study in which materials and telephone counseling were provided to first-degree relatives of melanoma patients, Geller et al [40] determined that the intervention lead to significantly higher rates of skin selfexamination among relatives who received the materials and counseling compared with relatives who underwent usual care with no intervention. First-degree relatives of melanoma patients, who are at particularly high risk, warrant targeted public health action.…”
Section: Families With a Member With A Melanoma Diagnosismentioning
confidence: 99%